DISCLOSURE QUALITY OF THE FINANCIAL INSTRUMENTS AND THE COST OF DEBT ON PORTUGAL, IRELAND, GREECE AND SPAIN - Pais, C. (XVI Encuentro AECA (Recuperação económica: confiança e investimento na Europa, 2014)
A consequence of the 2008 financial crisis was the importance given to financial instruments, by virtue of having said that they were partly to blame the crisis. Also disclosures have been growing in importance and usefulness to stakeholders. Given the above, we study the relationship between the quality of mandatory disclosures about financial instruments and the cost of debt for countries most affected by the sovereign debt crisis, for the periods of 2011 and 2012. Our results lead us to conclude that there is evidence that increasing the quality of disclosures of financial instruments reduces the cost of debt.